Genic male sterility increases rice drought tolerance. (November 2021) - Wen, Jianyu; Zeng, Yafei; Chen, Yunping; Fan, Fengfeng; Li, Shaoqing
Highlights: New transcription repressor OsAL5 was identified in this work which can regulate both the drought stress and thermosensitive male sterility. We also identified the targets of OsAL5 in drought and fertility pathway. OsAL5 down regulates the expression of target negative-pressure regulators, further promote influence the drought tolerance of the thermo-sensitive male sterile rice. We bred a new elite two-line hybrid rice via modulating the expression OsAL5. We perfected the model of OsTMS5 regulating the fertility under different temperatures. Abstract: Plant fertility and resistance to stress environments are antagonistic to each other. At booting stage, fertility is often sacrificed for survive in rice under abiotic stress. However, the relationship between fertility and resistance at molecular level remains elusive. Here, we identified a transcription factor, OsAlfin like 5, which regulates the OsTMS5 and links both the drought stress response and thermosensitive genic male sterility. The OsAL5 overexpression plants (OE-OsAL5) became sensitive to temperature owning to the OsTMS5 that the OE-OsAL5 plants were fertile under low temperature (23 °C) and sterile under high temperature (28 °C). Significantly, the survival rate of OE-OsAL5 lines was higher than that of the wide-type (WT) under drought stress. Further experiments confirmed that the OsAL5 regulated both of the OsTMS5 and the down-stream drought-related genes by binding to the 'GTGGAG' element in vivo, revealing that the OsAL5 participated both in the drought stress response and thermosensitive genic male sterility in rice. These findings open up the possibility of breeding elite TGMS lines with strong drought tolerance by manipulating the expression of OsAL5 .